I Know What I Need – Thank You for Asking: A Model of Young Women’s Co-Creation for Internet Based SRH Promotion - Sousa, Darinka Manuela (Auckland University of Technology, 2022)
This project, titled “I know what I need – Thank you for asking”, aimed to address the sexual and reproductive health needs of young women diaspora from the Indian subcontinent in Aotearoa New Zealand, by providing an innovative space to co-create internet-based sexual and reproductive health (SRH) promotion consisting of information and advice. It was relevant due to the large number of young women from the Indian subcontinent migrating to New Zealand for work and family reasons, which reflects a global trend. These young women may be caught within the paradox of experiencing two contrasting cultures: a more sexually open society in New Zealand and a culturally driven sexually restrictive society in their home countries. Experiencing such a paradox can make it challenging for young women diaspora from the Indian subcontinent without appropriate support systems. Traditional health education consists of brochures and pamphlets. While they have served as excellent tools for the dissemination of health infomation, the internet now presents more opportunities. Internet-based tools such as social media platforms (i.e., YouTube and Instagram) are free to use and, therefore, hold significant potential in the future of health promotion. These tools also allow information to be broadcast in real-time and can reach wider populations within a short span. Additionally, large audiences follow many “Influencers” and “YouTubers” as they relate to them and present an excellent opportunity for health promotion. Perhaps most exciting of all, they offer opportunities for users or consumers to become producers in a prosumer revolution. Feminism was chosen as the theoretical perspective as young women from the Indian subcontinent have traditionally lacked a voice. Furthermore, feminism, as a type of change-oriented critical theory, aims to result in social change. Being a young Indian woman myself, and having experienced a lack of voice, I wanted to conduct research so that young women, like me, could express their needs. The project utilised co-creation to develop SRH promotion ideas and tools as a group of young women. The research team consisted of myself, as a primary researcher from the community; and 5 participants (co-researchers) who were young women diaspora from the Indian Subcontinent residing in New Zealand. I decided to use Participatory Action Research (PAR) processes for the co-creation of internet-based SRH promotion ideas and tools. Co-creation focus groups were employed for data generation. Co-creation models can be influential as they are created with the active participation of the community. Therefore, they are more acceptable to them, and the project would have a more significant impact. The findings indicated that young women experienced a lack of sexual health discourse in their life journeys. This finding was not unexpected as young women from the Indian subcontinent lack access to sex education and other forms of SRH promotion. Discomfort in talking about sex can also lead to a significant lack of informed decision making regarding SRH. The analysis highlighted the scope to improve reproductive health outcomes through increased knowledge about the changes occurring in the reproductive system, an awareness of reproductive services available, and the means to access them. Furthermore, the findings revealed that young women desire more control through informed decision making and the gain of sexual rights. The internet has supported young women to gain access to such powers. Therefore, an internet-based tool could be beneficial to improve SRH outcomes for the community. Additionally, the findings suggested that the young women co-researchers felt empowered through participation in the project. Co-creation projects can lead to the empowerment of participants resulting in social change. The outcome of this project was the development by the primary researcher of an SRH promotion framework that could support and inform similar co-creation projects in the future. The framework was based on the data gathered in the field work, the reflections of the research team, and my experience as a public health practitioner. Such a framework could be beneficial in the planning of future health promotion, policies, and practices.
Keywords: Health promotion; Co-creation; Indian Subcontinent; Young women; Sexual and reproductive health